Comparative differential scanning calorimetric analysis of vegetable oils: II. Effects of cooling rate variation - Che Man, Y.B.; Tan, C.P. (John Wiley and Sons, 2002)
The effects of scanning rates (1, 5, 10 and 20°C/min) on the DSC cooling profiles of 11 vegetable oils have been determined in order to monitor peak transition temperatures, onset temperatures and crystallisation enthalpies. Triacylglycerol (TAG) profiles and iodine value analyses were used to complement the DSC data. The melted samples exhibited complicated crystallising exotherms. As the cooling rate increased, the crystallisation temperature decreased and the breadth of the crystallisation exotherm on cooling from the melt increased. In addition, the intensity of the exothermic peak increased somewhat when the cooling rate was increased. At slow cooling rates, TAG had more time to interact. It is conceivable that, at a low cooling rate (1°C/min), a prominent exotherm would be observed on crystallisation of vegetable oils and fats. The occurrence of one exotherm upon cooling indicated the co-crystallisation of the TAG upon slow cooling. On the basis of the corollary results obtained, vegetable oils may be differentiated by their onset temperature (Ton) values in the DSC cooling curves. Generally, there was a shift of Ton toward lower values with increasing cooling rates.